Hypoxia-induced structural changes in the media and adventitia of the rat hilar pulmonary artery and their regression. - Meyrick, B. (1980)
Chronic hypobaric hypoxia induces structural features characteristic of pulmonary hypertension, but little is known of their reversal. In the present study, rats have been exposed to hypobaric hypoxia for 10 days and subsequently allowed to recover in room air for 3, 14, 28, or 70 days. With the use of 1-mu sections and electron-microscopic and point-counting techniques, the regression of the medial and adventitial changes in the rat hilar intrapulmonary artery has been followed. In the media, 10-day hypoxia causes more than a doubling in thickness due to 1) hypertrophy of smooth muscle cells, particularly of rough sarcoplasmic reticulum and Golgi apparatus; 2) an increase in extracellular connective tissue, microfibrils, collagen fibers, and elastin, and 3) edemalike fluid. In addition, the elestic laminas are doubled in thickness, and myofilamentous processes of the hypertrophied smooth muscle cells contact them. After just 3 days' recovery, some cells have already returned to normal diameter, although medial thickening is unchanged. By Day 14 and at Days 28 and 70 of recovery, medial thickness and cell diameter are within the normal range, and by recovery Day 70, there is a significant increase in the relative areal proportion of extracellular collagen fibers and a decrease in elastin (P less than 0.001). Hypoxia also produces a more than twofold increase in adventitial thickness. Hypertrophy of fibroblasts and an increase in their number contribute to the thickening, as does as increase in collagen fibers. During 3-70 days of recovery, thickness is gradually reduced to normal levels, although it is still significantly above normal at Days 3, 14, and 28. The increases in thickness at these times are due mainly to the accumulation of collagen fibers, which are still apparent after 70 days of recovery. Thus, hypoxia causes a doubling in thickness of the medial and adventitial coats of the hilar muscular pulmonary artery, which with recovery regain near normal thickness but whose structure is altered. The increase in collagen fibers contributes to contracture and reduced distensibility in these vessels, which is apparent in arteriograms as narrowed lumen diameter.